2017
DOI: 10.1007/s10915-017-0388-9
|View full text |Cite
|
Sign up to set email alerts
|

Fast Iterative Method with a Second-Order Implicit Difference Scheme for Time-Space Fractional Convection–Diffusion Equation

Abstract: In this paper we want to propose practical numerical methods to solve a class of initial-boundary problem of time-space fractional convection-diffusion equations (TSFCDEs). To start with, an implicit difference method based on two-sided weighted shifted Grünwald formulae is proposed with a discussion of the stability and convergence. We construct an implicit difference scheme (IDS) and show that it converges with second order accuracy in both time and space. Then, we develop fast solution methods for handling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 61 publications
0
64
0
Order By: Relevance
“…Then by resorting to LMI in Matlab Toolbox, Theorem 3.1 can guarantee the outer synchronization of the dynamical networks, and we can derive the feasible solution to LMIs in (8) and (9) From these simulations, one can conclude that using the proposed method in this paper, outer synchronization of systems (1) and (4) can be achieved.…”
Section: Illustrative Examplementioning
confidence: 90%
“…Then by resorting to LMI in Matlab Toolbox, Theorem 3.1 can guarantee the outer synchronization of the dynamical networks, and we can derive the feasible solution to LMIs in (8) and (9) From these simulations, one can conclude that using the proposed method in this paper, outer synchronization of systems (1) and (4) can be achieved.…”
Section: Illustrative Examplementioning
confidence: 90%
“…Actually, the closed-form analytical solutions of FPDEs can be obtained in a few special cases [5], but such solutions are usually impractical. It thus becomes imperative to study the numerical solutions of FPDEs, and numerous reliable numerical methods have been developed [6][7][8][9][10][11][12][13][14][15][16][17]. Due to the nonlocality of the fractional operators, using the finite difference method to solve space/time-space fractional differential equations leads to a time-stepping scheme with dense coefficient matrices.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8]. In these models, the fractional diffusion equation (FDE) has been studied by many researchers, see [9][10][11][12][13][14][15][16][17][18] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme efficiently reduces the computational storage and cost for solving the time FDEs. Although there are many studies on the space/time FDEs, numerical studies on space-time FDEs are still not extensive, the readers are suggested to see [11,[38][39][40] and references therein.…”
Section: Introductionmentioning
confidence: 99%